Moderating role of organisational learning and firm size on risk management maturity in construction firms - Wang, Chen; Alashwal, Ali Mohammed; Asef, Arash; Abdul-Rahman, Hamzah; Wood, Lincoln Christopher (African Online Scientific Information Systems, 2018)
Background: It is not known whether organisational practice of learning and risk management maturity (RMM) varies based on firm size. Literature in the construction field lacks empirical studies on intervening influence of firm size on RMM. Objectives: This study aims to determine the significant factors influencing RMM by considering four dimensions of organisational learning (OL): information acquisition, knowledge dissemination, shared interpretation and organisational memory. Method: We tested the theoretical model in construction companies in Kuala Lumpur and Selangor states, Malaysia. There were 1000 questionnaires dispatched by mail and email to managers in the targeted firms. The component-based approach, also known as the partial least square (PLS) method, was used for data analysis. Results: Hierarchical regression analysis affirmed the influence of ten variables of OL on RMM while controlling the influence of firm size. Regardless of the firm size, the identified factors of OL can play an important role in enhancing the ability of construction organisations to attain better risk management practice. Conclusion: Construction firms seeking higher RMM should consider OL practices. The identified ten factors of OL are considered the vehicle to move the organisations to a new level of maturity. Particularly, firms should focus on two aspects of OL: information acquisition and shared interpretation. It can be deduced, therefore, that the more a firm acquires and interprets information related to project risk, the higher level of RMM the firm can achieve. In addition, effective learning through information gathering and interpretation could have a positive impact on risk management practices.